Safety assessment of the substances ‘wax, rice bran, oxidised’ and ‘wax, rice bran, oxidised, calcium salt’ for use in food contact materials - EFSA Panel on Food Contact Materials (FCM); Claude Lambré; Riccardo Crebelli; Maria daSilva; Konrad Grob; Evgenia Lampi; Maria Rosaria Milana; Marja Pronk; Mario Ščetar; Georgios Theodoridis; Els Van Hoeck; Nadia Waegeneers; et al. (EFSA Journal, 2024)
Abstract The EFSA Panel on Food Contact Materials (FCM) assessed the safety of the substances ‘wax, rice bran, oxidised’ and ‘wax, rice bran, oxidised, calcium salt’, used as additives up to 0.3% in polyethylene terephthalate (PET), polyamide (PA), thermoplastic polyurethane (TPU), polylactic acid (PLA) and poly(vinyl chloride) (PVC) in contact with all food types for long‐term storage at room temperature and below, after hot‐fill and/or heating. The substances consist of the chemical classes wax esters, carboxylic acids, alcohols and calcium salts of acids, along with an unidentified organic fraction up to ■■■■■ w/w. Migration into 10% ethanol and 4% acetic acid was below 0.012 mg/kg for each chemical class, and about 0.001 mg/kg for the unidentified fraction. In isooctane, migration was up to 0.297 mg/kg food for wax esters, below 0.01 mg/kg food for the other chemical classes and about 0.02 mg/kg food for the unidentified fraction. The contact with dry food and food simulated by 20% ethanol were considered covered by the migration tests with aqueous simulants. Based on genotoxicity assays and compositional analyses, the constituents of the chemical classes did not raise a concern for genotoxicity. The potential migration of individual constituents or groups of chemically‐related compounds of the unidentified fraction would result in exposures below (for aqueous food) and above (for fatty food) the threshold of toxicological concern for genotoxic carcinogens. Therefore, the FCM Panel concluded that the substances are not of safety concern for the consumer, if used as additives up to 0.3% w/w in PET, PLA and rigid PVC materials and articles intended for contact with all food types except for fatty foods, for long‐term storage at room temperature and below, including hot‐fill and/or heating up to 100°C for up to 2 h.